2010
DOI: 10.1159/000312538
|View full text |Cite
|
Sign up to set email alerts
|

Results of Electrocochleography in Ménière’s Disease after Successful Vertigo Control by Single Intratympanic Gentamicin Injection

Abstract: In the last several years, a promising new approach has been suggested in the therapy of Ménière’s disease (MD): the low-dose intratympanic gentamicin therapy. By titrating the desired vestibular inhibition by single injections and infrequent administration, side effects concerning hearing can be held on an acceptably low level, while disease-related symptoms are often successfully eliminated. However, it is still unclear if endolymphatic hydrops actually decreases when the patients become symptom free. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…However, little is known about the effect of gentamicin upon the function of transitional cells, which merits further study. This hypothesis is supported by the recent MRI study by Fiorino [2012] and electrocochleography results [Büki et al, 2011]. …”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…However, little is known about the effect of gentamicin upon the function of transitional cells, which merits further study. This hypothesis is supported by the recent MRI study by Fiorino [2012] and electrocochleography results [Büki et al, 2011]. …”
Section: Discussionsupporting
confidence: 68%
“…In the past few years, alternative measurements of endolymphatic hydrops have been tried in clinical practice, such as MRI scanning and electrocochleography [Büki et al, 2011; Fiorino et al, 2012]. A 3D-FLAIR sequence in 3 T MRI units, after intratympanic gadolinium administration had been used to visualize endolymphatic hydrops indirectly, relying on the imaging of the enlarged space occupied by nongadolinium-enhanced fluid space, reduced the area/volume of the gadolinium-enhanced perilymphatic compartments [Nakashima et al, 2007; Naganawa et al, 2011].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The elevation of SP amplitude in ears with endolymphatic hydrops appears to depend mainly on the mechanoelectrical transduction process into the cochlea, due to the loss of hair cells or to potassium poisoning of the perilymph, instead of the mechanical factor of the displacement of the basilar membrane. 22 Moon et al noted that patients with abnormal SP/AP exhibited significant elevation in their hearing thresholds compared with those who had SP/AP within the normal range, suggesting that MD patients with severe endolymphatic hydrops suffer more severe hearing deterioration over time 23 ---data corroborated by Ge et al 23 Lopes assessed the sensitivity and specificity of SP/AP ratio and the graphic angular measure in electrocochleography studies of 71 ears (41 MD patients and 14 healthy controls). This author concluded that the graphic angular measure is not sensitive and specific enough for the diagnosis of MD.…”
Section: Discussionmentioning
confidence: 99%